Nasionalisme Kebangsaan Sebagai Spirit Perjuangan Tokoh Pejuang di Lombok Timur 1945-1949 - Abdul Rasyad; Badarudin; Lalu Murdi; Jujuk Ferdianto (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2021)
The struggle of the Indonesian people to achieve independence from the colonialists is as old as colonialism itself. The struggle for independence had at least begun since the establishment of the late 19th century as a chain of struggle for the people in various regions in the archipelago. The struggle of the people of East Lombok in opposing colonialism is a historical record that complements the history of the national struggle of the Indonesian nation and does not have any meaning for the national struggle of the nation. This struggle is also a very strong bond to reach the culmination point of the struggle, namely the Proclamation of Independence on August 17, 1945, as well as efforts to defend Indonesia's independence until 1950. This study has a fundamental contribution in understanding historical information related to nationalism and the spirit of struggle for warriors in East Lombok. History, in this case the revolution in East Lombok in 1945-1949, has a dedactic value for the current and future generations of the nation. The educational value that can be learned from these historical events is at least that the nation's generation has mental strength both biologically and psychologically in facing all the challenges of life and has a high sense of nationalism as part of Indonesian society that must uphold the name of the Indonesian nation.